Methanosarcina plays a main role during methanogenesis of high-solids food waste and cardboard. (June 2018) - Capson-Tojo, Gabriel; Trably, Eric; Rouez, Maxime; Crest, Marion; Bernet, Nicolas; Steyer, Jean-Philippe; Delgenès, Jean-Philippe; Escudié, Renaud
Graphical abstract: Highlights: Methane production only achieved when Methanosarcina was present in the inoculum. Higher substrate loads were tolerated with higher initial Methanosarcina proportions. Independently of the inoculum, Methanosarcina was predominant in the digestates. Methanosarcina allowed a successful overload recovery. Abstract: Anaerobic digestion of food waste is a complex process often hindered by high concentrations of volatile fatty acids and ammonia. Methanogenic archaea are more sensitive to these inhibitors than bacteria and thus the structure of their community is critical to avoid reactor acidification. In this study, the performances of three different inocula were compared using batch digestion tests of food waste and cardboard mixtures. Particular attention was paid to the archaeal communities in the inocula and after digestion. While the tests started with inocula rich in Methanosarcina led to efficient methane production, VFAs accumulated in the reactors where inocula initially were poor in this archaea and no methane was produced. In addition, higher substrate loads were tolerated when greater proportions of Methanosarcina were initially present in the inoculum. Independently of the inoculum origin, Methanosarcina were the dominant methanogens in the digestates from the experiments that efficiently produced methane. These results suggest that the initial archaeal composition of the inoculum is crucial during reactor start-up to achieve stable anaerobic digestion at high concentrations of ammonia and organic acids.